Investigation of Aviation Lubricant Aging under Engine Representative Conditions. Issue 3 (4th May 2021) - Sheikhansari, Abdolkarim; Alborzi, Ehsan; Parks, Christopher; Siouris, Spiridon; Blakey, Simon
Abstract: Measurement of the antioxidant additives during lubricant thermal degradation is a useful method for providing a quantitative basis to understand the performance of the lubricant. In this study, a synthetic ester-based aviation oil was thermally exposed for a period of 500 h under gas turbine aero engine representative conditions using a lubricant/system interaction simulator (L/SIS) test rig. Physical and chemical changes including kinematic viscosity, total acid number (TAN), and oil chemical composition were monitored during the experiment. The change in oil chemical composition, with a particular focus on antioxidant additives, was examined using gas chromatography–mass spectroscopy (GC-MS) techniques. The results indicate that the identified antioxidants in the lubricant, dioctyl diphenylamine (DODPA) and phenyl-α-naphthylamine (α-NPA), were consumed during the degradation process of the oil, with DODPA having a slightly higher depletion rate. Posttest analysis of the stressed samples showed an increase in viscosity and TAN of the lubricant oil in the course of the thermal exposure. Furthermore, the reaction of DODPA and α-NPA in an oil thermally degrading environment was compared using density functional theory (DFT). The calculations indicate a lower energy barrier for the reaction of oil with DODPA.